Accuracy of staging in early oesophageal cancer using high resolution endoscopy and high resolution endosonography: a comparative, prospective, and blinded trial. Issue 5 (13th April 2004) - May, A; Günter, E; Roth, F; Gossner, L; Stolte, M; Vieth, M; Ell, C
Abstract : Background and aims: The increasing use of endoscopic resection for curative treatment of early oesophageal cancers requires accurate staging before therapy. In a prospective blinded trial, we compared staging of early oesophageal carcinoma using high resolution endoscopy (HR-E) with staging using high resolution endosonography (HR-EUS). Patients and methods: A total of 100 patients (89 men, 11 women; mean age 63.9 (10.8) years (range 31–91)) with a suspicion of early oesophageal adenocarcinoma (n = 81) or squamous cell carcinoma (n = 19) were enrolled in the study. After endoscopic staging with high resolution video endoscopy by two experienced endoscopists, HR-EUS was performed by an experienced endosonographer who was blinded to the endoscopic assessment. Results of the staging examinations were correlated with the histology of the resected tumours. Results: Overall rates for accuracy of the endoscopic and endosonographic staging were 83.4% and 79.6%, respectively. Sensitivity for mucosal tumours (n = 68) was more than 90% (EUS 91.2%, endoscopy 94.1%) while sensitivity for submucosal tumours (n = 25) was lower, at 48% for EUS and 56% for endoscopic staging. A combination of the two techniques increased the sensitivity for submucosal tumours to 60%. Submucosal tumours in the tubular oesophagus were significantly better staged with HR-EUS than submucosal tumours close to the oesophagogastric junction (10/11 v 2/14; p<0.001). Tumours infiltrating the second and third submucosal layers were also more correctly diagnosed than tumours with slight infiltration of the first submucosal layer (sm1). Conclusions: The overall diagnostic accuracy of both HR-E and HR-EUS with a 20 MHz miniprobe in early oesophageal cancer was high (approximately 80%), with no significant differences between the two techniques. HR-E and HR-EUS provide a high level of diagnostic accuracy for mucosal tumours and submucosal tumours located in the tubular part of the oesophagus. With submucosal tumours located at the oesophagogastric junction or with infiltration of the first third of the submucosa however, the diagnostic accuracy of both techniques is not yet satisfactory.